Pruritic Scalp. Issue 5 (September 2018) - Limone, Brittanya A.; Moncrieff, Norma; Jacob, Sharon E.
Abstract : ABSTRACT: Teledermatology is a term to describe the provision of dermatologic medical services through telecommunication technology. This is a case of a pruritic scalp in a child.